2019
DOI: 10.3389/fcimb.2019.00229
|View full text |Cite
|
Sign up to set email alerts
|

Miltefosine-Lopinavir Combination Therapy Against Leishmania infantum Infection: In vitro and in vivo Approaches

Abstract: Concurrently, leishmaniasis and AIDS are global public health issues and the overlap between these diseases adds additional treats to the management of co-infected patients. Lopinavir (LPV) has a well characterized anti-HIV and leishmanicidal action, and to analyze its combined action with miltefosine (MFS) could help to envisage strategies to the management of co-infected patients. Here, we evaluate the interaction between LPV and MFS against Leishmania infantum infection by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…The early efforts to overcome these limitations were directed to the improvement of the drug delivery systems 27 , 28 and the formulation of more effective combination therapies. 29 However, the cost increase 30 − 32 and the rapid recurrence of resistance phenomena 33 37 prompted the scientific community to turn its attention toward the development of new antileishmanial drugs, 38 − 51 which should be effective, safe, and not expensive. Concerning the research and development of new improved drugs, four main approaches are exploited: (i) drug repurposing, as in the case of fexinidazole 40 ( Figure 2 ); (ii) diversity-oriented screening of collections of chemicals, such as oxaborole AN-4169 ( 39 , 52 ) and aminopyrazole amide 1 ( 39 ) ( Figure 2 ); (iii) phenotypic screening, leading to the identification of new biological targets and effective inhibitors, 53 56 such as 17-AAG (HSP90 inhibitor) 57 ( Figure 2 ); and (iv) use of known or new natural products with limited side effects, 58 61 especially those deriving from plants, such as fucoidan 58 and 11,13-dehydrocompressanolide 61 ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The early efforts to overcome these limitations were directed to the improvement of the drug delivery systems 27 , 28 and the formulation of more effective combination therapies. 29 However, the cost increase 30 − 32 and the rapid recurrence of resistance phenomena 33 37 prompted the scientific community to turn its attention toward the development of new antileishmanial drugs, 38 − 51 which should be effective, safe, and not expensive. Concerning the research and development of new improved drugs, four main approaches are exploited: (i) drug repurposing, as in the case of fexinidazole 40 ( Figure 2 ); (ii) diversity-oriented screening of collections of chemicals, such as oxaborole AN-4169 ( 39 , 52 ) and aminopyrazole amide 1 ( 39 ) ( Figure 2 ); (iii) phenotypic screening, leading to the identification of new biological targets and effective inhibitors, 53 56 such as 17-AAG (HSP90 inhibitor) 57 ( Figure 2 ); and (iv) use of known or new natural products with limited side effects, 58 61 especially those deriving from plants, such as fucoidan 58 and 11,13-dehydrocompressanolide 61 ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Miltefosine is a drug used to treat leishmaniasis [22,58]. It has been shown to be effective against various parasite species, such as those causing visceral leishmaniasis and/or tegumentary leishmaniasis [8,19,44]. However, recent reports have shown that miltefosine can cause adverse effects such as nausea and vomiting during and/or after administration as well as teratogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, miltefosine was administered to a BALB/c model infected with L . (L.) infantum (MHOM/MA67ITMAP263) and resulted in 100% suppression of the parasite burden in liver and spleen at 7.7 mg/kg (Rebello et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A two-step washing procedure was performed to eliminate non-adherent cells. Promastigotes were added at a ratio of 10:1, using RPMI 1640 supplemented with 2% horse serum (Rebello et al, 2019), and after 4 h, the extracellular parasites were removed by washing; fresh medium containing SERT, LP-SERT, and control were added; and the cells were incubated at 37°C for 72 h. The initial concentration of SERT and miltefosine was 100 μM, and that for LP-SERT was 20 μM. At the end of the assay, the slides were stained with Giemsa and observed using a light microscopy.…”
Section: Methodsmentioning
confidence: 99%